The Influence of Ethical Leadership on Ethical Behavior Mediated by Ethical Climate at Government Institutions in Aceh Indonesia - Nurainun Samka; Syafruddin Chan; Heriyana Heriyana; Rasyimah Rasyimah (Management Research and Behavior Journal, 2021)
The objective of this study is to identify the influence of ethical leadership on the ethical behavior of government officers in Aceh Province that mediated by ethical climate. The ethical leadership variable of moral person and moral manager are employed as exogenous variables, while the ethical leadership is as endogenous variable, then the ethical climate of caring and law and code is employed as both mediation and exogenous variables. The subject of this research is the officers in several government institutions in Aceh Province. The data was collected through a survey method and the hypotheses were tested using Structural Equation Modeling (SEM). The result of this study identified that ethical leadership has positive influence on ethical climate and there is a direct influence of ethical leadership on ethical behavior. However, the influence between ethical leadership and ethical behavior of the officers is not mediated by ethical climate.